An integration of brain-computer interfaces with an alternative augmentative communication system - Díaz, Francisco Javier (2023)
People who cannot communicate with others or that have great difficulty in doing so are usually dependent beings and suffer from social isolation. There are multiple systems and tools that enhance the communicative interactions, called Alternative and Augmentative Communication Systems (AACS). In critical situations, where no voluntary movements are available, Brain-Computer Interfaces (BCI) start to take part. BCI’s are devices that allow a person to interact with a computer using only their neuronal activity. BCI’s have been studied for more than 30 years, but their high error rate and the complexity of the systems have always been challenges when implementing functional reallife solutions. The current work includes a review of the BCI Emotiv Epoc, a wireless, low-end, EGC device that tries to bring medical-lab technology to the users’ home, as well as the development of a custom application to connect it to a well-known AACS: ACAT.